Pengaruh Teknik Pictorial Riddle terhadap Kreativitas Mata Pelajaran IPS Kelas V SDN 104215 Sudirejo - Ginting, Roynoaldy; Pulungan, Lilik Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to enhance students' learning creativity by applying the pictorial riddle model in social studies education. The study uses a qualitative method. The subjects in this study are all fifth-grade students at SDN 104215 Sudirejo, Namorambe District, Deli Serdang Regency, totaling 23 students. The data source in this study is all fifth-grade students at SDN 104215, and the student data collected is in the form of learning test results. The teacher, as the researcher, focuses on the teacher's activities in teaching and the interaction between the teacher and the students in the learning process. The results of this study show that the application of the pictorial riddle model (the key to success) in social studies education can improve students' learning outcomes and creativity. The pretest data before using the pictorial riddle model showed an average score of 72.52, while based on the posttest results after using the pictorial riddle model, there was an average score of 87.39, indicating an improvement. This is also evidenced by the number of students who achieved the minimum passing grade before the research was conducted.